ROLE OF DISRUPTIVE TECHNOLOGY IN MAKING FINANCIAL SERVICES EFFECTIVE: A QUANTITATIVE INVESTIGATION OF EXPERT’S OPINION - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana; Kiran Singh, Shoraisam (The journal of contemporary issues in business and government, 2022)
The financial sector is undergoing a vast transformation. It used to be physical, and now it uses I.T. and big data techniques and unique human capital. Before the transformation started, the financial sector started becoming intertwined with a high proportion of the intermediary activities and started getting market-based. For instance, banks face higher competition from the other intermediaries and increased digital services in core businesses like advisory and payment services. Many changes in using technology for developing new business models and services have been emerging with a rise in FinTech services. This can be easily understood as modern-day innovative information technology in the financial sector increases day by day. The speed with which different types of new digital innovations are being adopted and the acquisition of the users has increased markedly.